Seed germination and growth of maize (Zea mays L.) on lead contaminated soil in response to compost, exogenous proline and plant growth promoters in Ibadan, Nigeria (2018)
Soil contamination with heavy metal poses serious threat to agricultural productivity. It induces oxidative stress on crop and causes reduction in crop yield. To enhance crop production and safety, strategies must be developed to increase crop tolerance to heavy metal toxicity and enhance crop productivity on contaminated sites. Study was carried out to determine the ability of exogenous application of proline, hormones and compost in ameliorating the effect of lead (Pb) stress on maize crop grown on lead-acid battery wastes contaminated soil. The experiment was laid out in a Completely Randomized Design (CRD) and replicated three times. The treatments were proline (P), indole acetic acid (IAA), gibberellic acid (GA), and compost. Proline and hormones were applied at 0, 5 and 10 mM as seed soaking while compost was applied to the soil two weeks before planting using 0, 20 and 40 t/ha application rates. These were applied individually and in combination to give a total of 34 treatments including, control and replicated 3 times. Un-amended contaminated and uncontaminated soil served as checks. The experiment was terminated eight weeks after planting. Data were collected on maize percentage germination, duration of survival of maize seedlings, growth parameters and dry matter yield. Maize seeds pre-treated with P at 10 mM and C (40 t/ha) and those treated with GA (5 mM) + C (20 t/ha) gave 100% germination on contaminated soil. Compared to contaminated control, duration of survival, maize growth and dry matter yield were enhanced when seeds were pre-treated with exogenous proline and hormone and gown on contaminated soil amended with compost. Seed treatment with 10 mM P + 20 t/ha compost generally increased plant height, number of leaves, stem girth and leaf area relative to control and IAA treatments. Pre-sowing seed treatment with 10 mM P and soil amendment with 40 t/ha compost increased the maize dry matter yield better than other treatments, including control. Maize growth and yield on lead-contaminated soil were enhanced with seed pre-treatment with 10 mM proline and 40 t/ha compost. Exogenous application of proline and gibberellic acid in combination with compost enhanced maize germination, growth and yield in Pb contaminated soil and alleviate Pb toxicity.